Formulasi dan Uji Stabilitas Fisik Sediaan Permen Jeli Ekstrak Wortel (Daucuscarota L.): Formulation and Physical Stability Tests of Carrot Extract Jelly Candy (Daucus carota L.) - Resti Hayu Ningtyas; Agitya Resti Erwiyani (Universitas Ngudi Waluyo, 2023)
Carrots contain vitamin A and Î²-carotene which help maintain eye health. The content of carotenoids in carrots can protect DNA, protein, and fat from oxidative damage and plays a role in maintaining the normal function of the immune system, skin, mucous membranes, and eye vision function. Carrots are formulated in the form of jelly candy as an eye supplement. The aim of this study was to evaluate the characteristics and physical stability of carrot extract jelly candy preparations. Jelly candy was made with various concentrations of gelatin as a jelly former of 8%, 10%, 12%, 14%, 16%, and 18%. Tests for physical characteristics were carried out including organoleptic tests, weight uniformity, pH, water content, and panelist tests. A stability test was observed at room temperature for 7 days. The jelly candy has a characteristic orange color, star shape, distinctive mango aroma, and sweet taste. Jelly candy has a pH of 5 with a weight in the range of 4.17 g - 4.94 g. The water content in each jelly candy is in the range of 38.67% - 48.03%. The panelist test had the highest elasticity at a concentration of 14%, the most attractive color, and shape at a concentration of 18%, smell and taste at a concentration of 8%, 10%, 14%, 16%, and 18% had the same score. The results of the stability test for 7 days showed that the jelly candy experienced a decrease in weight and pH uniformity, mold growth on the surface of the candy, and the water content did not meet the requirements. ABSTRAK Wortel memiliki kandungan vitamin A dan Î²-karoten yang membantu menjaga kesehatan mata. Kandungan karotenoid dalam wortel dapat melindungi DNA, protein, dan lemak dari kerusakan oksidatif serta berperan dalam mempertahankan fungsi normal sistem imun, kulit, membran mukosa, dan fungsi penglihatan mata. Wortel diformulasi dalam bentuk permen jeli sebagai suplemen mata. Tujuan penelitian ini mengevaluasi karakteristik dan stabilitas fisik sediaan permen jeli ekstrak wortel. Permen jeli dibuat dengan variasi konsentrasi gelatin sebagai pembentuk jeli sebesar 8%, 10%, 12%, 14%, 16%, dan 18%. Pengujian karakteristik fisik dilakukan meliputi uji organoleptis, keseragaman bobot, pH, kandungan air, dan uji panelis. Uji stabilitas dilakukan pengamatan pada suhu kamar selama 7 hari. Permen jeli memiliki karakteristik warna orange, berbentuk bintang, aroma khas mangga dan rasanya manis. Permen jeli memiliki pH 5 dengan bobot berada pada rentang 4,17 g - 4,94 g. Kandungan air pada masing-masing permen jeli berada pada rentang 38,67% - 48,03%. Uji panelis kekenyalan tertinggi pada konsentrasi 14%, warna dan bentuk yang paling menarik pada konsentrasi 18%, bau dan rasa pada konsentrasi 8%, 10%, 14%, 16%, 18% memiliki skor yang sama. Hasil uji stabilitas selama 7 hari menunjukkan permen jeli mengalami penurunan pada keseragaman bobot dan pH, serta kandungan air tidak memenuhi persyaratan.